NK Cells in Autoimmune Diseases: Protective or Pathogenic? - Liu, Meifang; Liang, Shujuan; Zhang, Cai (Frontiers in Immunology, 2021)
Autoimmune diseases generally result from the loss of self-tolerance (i.e., failure of the immune system to distinguish self from non-self), and are characterized by autoantibody production and hyperactivation of T cells, which leads to damage of specific or multiple organs. Thus, autoimmune diseases can be classified as organ-specific or systemic. Genetic and environmental factors contribute to the development of autoimmunity. Recent studies have demonstrated the contribution of innate immunity to the onset of autoimmune diseases. Natural killer (NK) cells, which are key components of the innate immune system, have been implicated in the development of multiple autoimmune diseases such as systemic lupus erythematosus, type I diabetes mellitus, and autoimmune liver disease. However, NK cells have both protective and pathogenic roles in autoimmunity depending on the NK cell subset, microenvironment, and disease type or stage. In this work, we review the current knowledge of the varied roles of NK cell subsets in systemic and organic-specific autoimmune diseases and their clinical potential as therapeutic targets.